Da diversidade da loucura à identidade da cultura: o movimento social cultural no campo da reforma psiquiátrica/ From madness diversity to cultural identity: social and cultural movement inside psychiatric reform field - Amarante, Paulo; Freitas, Fernando; Nabuco, Edvaldo; Pande, Mariana Nogueira Rangel (Brazilian Journal of Mental Health, 2012)
Este artigo reflete sobre o processo de construção de práticas e políticas culturais no campo da saúde mental, aqui considerado como um campo artístico-cultural, que surge no âmbito do campo da atenção psicossocial e que tende à autonomia, isto é, que tende a se tornar um movimento social e cultural no sentido de contribuir para a transformação do imaginário social sobre a loucura. Realizado a partir de uma pesquisa, o artigo procura identificar as bases políticas e culturais do surgimento e a viabilidade desse novo campo. ABSTRACT This article reflects upon the construction process of cultural practices and policies in mental health field, here considered a artistic-cultural field that arises from within psychosocial attention field and that lends itself to autonomy, that is, tends to become a social and cultural movement as in contributing for transforming social imagination on madness. Carried out based on a research, the article intends to identify political and social foundations of this emergence and the viability of this new field. KEYWORDS: Cultural Diversity; Mental Health; Psychosocial Attention; Art; Culture.